2009
DOI: 10.1111/j.1365-2672.2009.04599.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous differential detection of human pathogenic and nonpathogenicVibriospecies using a multiplex PCR based ongyrB andpntA genes

Abstract: Aims:  To develop a multiplex PCR targeting the gyrB and pntA genes for Vibrio species differentiation. Methods and Results:  Four pairs of primers targeting gyrB gene of Vibrios at genus level and pntA gene of Vibrio cholerae, Vibrio parahaemolyticus, Vibrio vulnificus were designed. This PCR method precisely identified 250 Vibrio species and demonstrated sensitivity in the range of 4 × 104 CFU ml−1 (c. 200 CFU per PCR) to 2 × 103 CFU ml−1 (c. 10 CFU per PCR). Overall, the gyrB gene marker showed a higher spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
24
0
4
Order By: Relevance
“…In silico PCR as described previously was carried out prior to actual PCR evaluation to make sure the primers used are targeted to the correct loci (Teh et al, 2010;Thong et al, 2011). The forward and reverse primers are 5ꞌ-CTG GAG ACC ACT CCC ATC CTT TCT-3ꞌ and 5ꞌ-GAT GTG GCC ATC ACA TTC GTC AGA T-3ꞌ, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In silico PCR as described previously was carried out prior to actual PCR evaluation to make sure the primers used are targeted to the correct loci (Teh et al, 2010;Thong et al, 2011). The forward and reverse primers are 5ꞌ-CTG GAG ACC ACT CCC ATC CTT TCT-3ꞌ and 5ꞌ-GAT GTG GCC ATC ACA TTC GTC AGA T-3ꞌ, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PCR facilitates the identification of the strains that are viable but non-culturable [12] in this study 16S rRNA gene was amplified and showed great results. It is less labor intensive and much faster than conventional methods, and that is the reason of its increasing application among investigators [13]. The antibiogram profile revealed that isolates, all isolates showed multi-drug resistant to amoxicillin and nitrofurantoin.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiplex PCR is widely applied for the rapid diagnosis of many infectious diseases (20,31,32,34). With well-designed primers used under fully optimized conditions, most of the multiplex systems have shown high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The primers with the secondary structure were redesigned with slight modifications. The selected primers were then tested through a BLAST search and in silico PCR (http: //insilico.ehu.es/PCR/) as described previously for the prediction of amplicons (32,34). PCR conditions for each of the primer pairs were optimized individually and then mixed together to perform a multiplex PCR for the detection of five species of human malaria parasites.…”
Section: Microscopy Examinationmentioning
confidence: 99%